'A Mersshy Contree Called Holdernesse' excavations on the route of a national grid pipeline in Holderness, East Yorkshire : rural life in the Claylands to the East of the Yorkshire Wolds, from the Mesolithic to the Iron Age and Roman periods, and beyond - Glover, Gavin; Flintoft, Paul; Moore, Richard (Archaeologist) (Archaeopress, 2016)
26 sites were excavated on the route of a National Grid pipeline across Holderness, East Yorkshire. These included an early Mesolithic flint-working area, near Sproatley. In situ deposits of this age are rare, and the site is a significant addition to understanding of the post-glacial development of the wider region. Later phases of this site included possible Bronze Age round barrows and an Iron Age square barrow. Elsewhere on the pipeline route, diagnostic Mesolithic, Neolithic and Bronze Age flints, as well as Bronze Age pottery, provide evidence of activity in these periods